Importance of lightning detection network development in Peninsular Malaysia. Issue 1 (November 2019) - Islam, M.A; Chan, A.; Khaw, S. K. K.; Salleh, S. A.; Zakaria, N. H.; Isa, N.A.; Gee, M.O.C.; Azari, M.
Abstract: Lightning is a major climatic phenomenon in Southeast Asia over Indian Ocean and Malaysia is the most affected area in the region. Damages in the different industries, real estates, defense and human fatalities are caused by lightning strikes and it is very common in Malaysia. Existing non-effective lightning detection network in Malaysia now has become an urge to modify the system and improve it according to the need of the Malaysian Meteorological Department. Research facilities in the Malaysian universities and related research organizations need to give substantial effort in developing lightning science and technology to solve this problem. In this article, current status of lightning detection network in Malaysia and its weaknesses have been discussed briefly. Also, suggestion have been proposed to improve it.